G13(P) A prospective review of psychosocial functioning in parents of infants with complex congenital heart disease going home for the first time following first stage cardiac surgery. (27th April 2015) - Gaskin, KL; Barron, D; Rooney, M; Cooper, L; Mohammed, N
Abstract : Aim: The study presented here prospectively explores psychosocial adaptation and adjustment in parents going home for the first time with their infants following first stage cardiac surgery for complex congenital heart disease (CHD). Preliminary review of psychosocial functioning (anxiety, depression and confidence) and parent demographics in 15 parents (12 mothers, 3 fathers of 12 infants) enrolled into a feasibility study exploring the efficacy of home monitoring for infants born with complex CHD, will be presented. Method: Parents of infants being discharged from a specialist cardiac centre in the UK are recruited into a feasibility study, which commenced in August 2013 and ends in February 2015. The study is split into 3 randomisation arms: Group A were discharged home with weighing scales, a saturation monitor and a Congenital Heart Assessment Tool (CHAT); Group B were discharged home with the CHAT tool only and Group C were randomised to normal standard care. The parents are interviewed at 4 time points: T0 before discharge, T1 2 weeks post discharge, T2 8 weeks post discharge and T3 following the second surgical intervention (approximately 4–6 months post discharge). Baseline demographic data (family demographics, time of diagnosis, distance of specialist cardiac centre from home) is collected and parents are asked to complete the PHQ9, GAD7 and Maternal Confidence score (MCS) at each of the interviews. Results: A preliminary review of the data collected from 15 parents, has demonstrated an improvement in anxiety, depression and confidence scores for all parents. Whereas some scores showed significant improvement a minority have shown a minimal increase in confidence scores. A more in depth analysis is currently being undertaken and these results will be available for display at the conference. Conclusion: This is the first study of its kind to prospectively explore parents' psychosocial adaptation and adjustment during the transition from hospital to home following first stage cardiac surgery. Despite the small number of families recruited into the study so far, the results provide an important insight into the discharge care and support these parents require. Implications for practice will be discussed. Acknowledgement: Study in collaboration with Little Hearts Matter, Heart Research UK and Coventry University (sponsors).